Armed Forces in Law Enforcement Operations? - The German and European Perspective - Lioe, Kim Eduard; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
At the center of this study lies the allocation of responsibilities and the division of labor between the armed forces and the mission of the police as well as other security forces in Europe. The mission of these forces defines the demarcation line between the spheres of internal and external security by assigning the former to the police and the latter to the armed forces. The focal idea is the evaluation of the feasibility of a strict separation as maintained in Germany in a European context, practical difficulties in its application, and potential ways to overcome such difficulties. This comprises in particular a comparison of the "German Way" with other European states and the corresponding methods chosen against the background of joint operations abroad.
From the contents: Introduction -- Comparative Law -- Operational and Institutional Consequences -- Conclusion.
Keywords: Law; Law; International Humanitarian Law, Law of Armed Conflict; Private International Law, International & Foreign Law, Comparative Law